Early Ordovician trilobites from the Iruya area (Cordillera Oriental, northwestern Argentina) and their stratigraphic significance. (14th September 2016) - Tortello, M. Franco; Esteban, Susana B.
Abstract: The middle part of the Santa Rosita Formation (Tremadocian) is well exposed in the Iruya area, northwestern Argentina. At the Pantipampa and Rodeo Colorado localities, it is composed of shale and sandstone representing a wave-dominated shelf with influence of storm activity. Twenty-two trilobite species are described from these localities. Low-diversity assemblages from the lower part of the succession ( Kainella meridionalis Kobayashi, Asaphellus catamarcensis Kobayashi, Leptoplastides marianus [Hoek]) are diagnostic of the early Tremadocian Kainella meridionalis Zone. Trilobites from the middle part of the sequence are much more diverse. Kainella teiichii Vaccari and Waisfeld, Gymnagnostus kobayashii n. sp., Conophrys sp. indet., Asaphellus clarksoni n. sp., A . stenorhachis (Harrington), A . isabelae Meroi Arcerito, Waisfeld and Balseiro, Ogygiocaris ? iruyensis n. sp., Niobe ( Niobella ) inflecta (Harrington and Leanza) n. comb., Metayuepingia riccardii n. sp., Pseudokainella keideli Harrington, Apatokephalus rugosus n. sp., Onychopyge acenolazai n. sp., O . gonzalezae n. sp., Nileus cingolanii n. sp., N . erici n. sp., Leptoplastides marianus, Parabolinella sp. indet., Hapalopleura sp. indet., and Ceratopygidae gen. et sp. indet., occur at different levels of the Kainella teiichii Zone. This biostratigraphic unit includes the oldest records of Nileus Dalman and Ogygiocaris ? Angelin; Metayuepingia Liu, Niobe ( Niobella ) Reed, and Onychopyge Harrington are here first reported from the Tremadocian of southwest Gondwana. Finally, the uppermost part of the succession is characterized by the absence of the genus Kainella Walcott and the occurrence of Bienvillia tetragonalis (Harrington), Asaphellus stenorhachis, Pseudokainella keideli and Leptoplastides sp. indet., which are indicative of the middle Tremadocian Bienvillia tetragonalis Zone. The trilobites described in this paper provide a basis for the refinement of correlations with other Lower Ordovician sections of the Cordillera Oriental. The genera recognized have their closest affinities with faunas from Scandinavia, Great Britain, and China.